2014
DOI: 10.1088/2041-8205/795/1/l16
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Circular Polarization Survey in Star-Forming Regions: Correlations and Trends

Abstract: We have conducted a systematic near-infrared circular polarization (CP) survey in star-forming regions, covering high-mass, intermediate-mass, and low-mass young stellar objects. All the observations were made using the SIRPOL imaging polarimeter on the Infrared Survey Facility 1.4 m telescope at the South African Astronomical Observatory. We present the polarization properties of 10 sub-regions in 6 star-forming regions. The polarization patterns, extents, and maximum degrees of linear and circular polarizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Our previous studies, which have included a systematic near-infrared survey of circular polarization in star-forming regions of various luminosities, presented the relationships between luminosities, extents, and the degree of circular polarization. We found that a high degree of circular polarization, generated in some starforming regions, was consistent with a dichroic extinction mechanism (Chrysostomou et al 2007;Fukue et al 2009;Kwon et al 2013Kwon et al , 2014. Therefore, it is important to extend this survey for various star-forming regions, in particular bipolar nebulae such as GGD 27 IRS, and to determine how often significant circular polarization is observed.…”
Section: Introductionmentioning
confidence: 66%
“…Our previous studies, which have included a systematic near-infrared survey of circular polarization in star-forming regions of various luminosities, presented the relationships between luminosities, extents, and the degree of circular polarization. We found that a high degree of circular polarization, generated in some starforming regions, was consistent with a dichroic extinction mechanism (Chrysostomou et al 2007;Fukue et al 2009;Kwon et al 2013Kwon et al , 2014. Therefore, it is important to extend this survey for various star-forming regions, in particular bipolar nebulae such as GGD 27 IRS, and to determine how often significant circular polarization is observed.…”
Section: Introductionmentioning
confidence: 66%
“…One is photolysis of enantiomers by circularly polarized UV light (UV CPL) (39). UV CPL is also suggested as a possible interstellar mechanism for the production of EE (40,41). Laboratory experiments with UV CPL have demonstrated a slight preferential destruction of one enantiomer, which resulted in relatively small but reversible EE (depending on the direction of the CPL) from an initially racemic mixture of amino acids (39).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, circular polarization traces the overall geometry of the setup as well as properties of the medium. Examples include circular polarization of starlight [10] or of diffuse radiation in star-forming regions [11], and the circular polarization observed from solar system planets [12,13]. An alternative source of circular polarization (relevant for both foregrounds and new physics) involves magnetized media, where the intrinsic emission can be circularly polarized due to the preferred handedness of particle trajectories, as occurs in masers [14,15], GRB afterglows [16,17], and (we expect) in the diffuse synchrotron emission from our Galaxy.…”
mentioning
confidence: 89%
“…Due to our choice of thex-axis, no further rotation is necessary. 11 We follow the convention of CLASS for the transfer functions, e.g. T E = − 5 4 √ 6 (G (0) +G (2) ), see Eq.…”
Section: )mentioning
confidence: 99%